Bibliometric analysis of digital library in Indonesia 2014-2024 using Biblioshiny Bibliometrix - Ilyasa, Diaz; Winoto, Yunus; Rukmana, Evi Nursanti (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. This study understands the development of digital libraries in Indonesia in the 2014-2024 period using bibliometrics, along with the rapid internet penetration and the increasing number of digital libraries in Indonesia which have changed the way people access information. Data Collection Methods. This is a quantitative approach with a bibliometric analysis based on the Scopus bibliographic dataset with 162 publications with a keyword filtering process. Data Analysis. This is a bibliometric analysis using Biblioshiny Bibliometrix. Results and Discussion. This study shows that despite fluctuations, digital library research in Indonesia has increased, especially in 2017 and 2021, reflecting growing awareness during the COVID-19 pandemic, with a focus on